Beyond Adaptive Mental Functioning With Pain as the Absence of Psychopathology: Prevalence and Correlates of Flourishing in Two Chronic Pain Samples - Trompetter, Hester R.; Mols, Floortje; Westerhof, Gerben J. (Frontiers in Psychology, 2019)
Chronic pain outcomes are traditionally defined in terms of disability and illness. A definition of adaptive functioning in the context of chronic pain as more than the mere absence of negative outcomes, is the ability to flourish (i.e. experience high levels of emotional, psychological ánd social well-being; Keyes, 2002). We explored in two chronic pain samples the prevalence and sociodemographic, physical and psychological correlates of flourishing, in contrast to (being at risk for) psychopathology. Sample 1 (n=1498) was a nationally representative sample. Subgroups included people with regular joint pain (1), regular joint pain ánd rheumatoid arthritis (2) and without chronic pain (3). Chi-square tests were applied to calculate the prevalence of both mental health outcomes and examine if people with(out) chronic pain were more/less likely to flourish, or be at risk for psychopathology. Sample 2 (n=238) concerned baseline data of a Randomized Controlled Trial on the effectiveness of Acceptance & Commitment Therapy for chronic pain (Trompetter et al., 2015). We performed logistic regression analysis to identify flourishers and those at risk for depression. The Mental Health Continuum-Short Form was used in both samples to measure flourishing. The prevalence of flourishing in people with chronic pain was 36% in sample 1, and 22% in sample 2. Compared to those without chronic pain, people with chronic pain were as likely to flourish, but more likely to be at risk for psychopathology, In sample 2, both flourishing and being at risk for depression were related foremost to psychological correlates. While engaged living was the most important correlate of flourishing, pain catastrophizing and psychological inflexibility were most important correlates of being at risk for depression. We can conclude that people with chronic are able to flourish. Findings suggest that positive and negative chronic pain outcomes function on two different continua, with potentially unique protective and risk factors. The Psychological Flexibility model seems to provide pathways to explain both poor and optimal functioning in the presence of chronic pain. A better understanding of people with chronic pain who are able to flourish can be a fruitful endeavor to improve chronic pain interventions.